Chemical recycling and use of various types of concrete waste: A review. (15th February 2021) - Ho, Hsing-Jung; Iizuka, Atsushi; Shibata, Etsuro
Abstract: Concrete is one of the most widely used materials globally, and therefore huge amounts of concrete waste, which is usually strongly alkaline, are generated. Concrete waste recycling and use are essential to avoid negative environmental impacts, and a comprehensive literature review is required in this regard. Effective recycling and the use of chemicals in concrete waste could allow for a sustainable circular cement and concrete industry to be developed and could help solve various environmental problems. This review article assesses methods to recycle and reuse concrete waste to amend and stabilize soil, produce new construction materials, purify and neutralize water, treat gases, and sequester and use CO2 . It was noted that extensive improvements exist for chemical recycling and the use of concrete waste. The reactions and mechanisms that are involved in various methods were assessed. Some methods included signature reaction mechanisms, such as the formation of calcium hydroxyapatite, the pozzolanic reaction, and the desulfurization reaction, which is effective in concrete waste recycling and use. Concrete waste is one of the most promising candidates for CO2 sequestration and direct/indirect carbonation. The comprehensive literature survey as summarized in this review article suggests a promising research trend and confirms the importance of chemical recycling and use of concrete waste. Highlights: Concrete waste chemical recycling and use methods are reviewed. Reaction mechanisms involved in concrete waste recycling methods are assessed. Concrete waste uses to amend soil or produce new construction material are assessed. Concrete waste uses to purify water and gases are assessed. Concrete waste mineral carbonation to sequester and use CO2 is assessed.